2006
DOI: 10.1016/j.ssci.2005.08.019
|View full text |Cite
|
Sign up to set email alerts
|

Effects of planar and non-planar driver-side mirrors on age-related discomfort-glare responses

Abstract: In this study, we evaluated subjective nighttime discomfort-glare responses on three different types of planar and non-planar driver-side mirrors on two age groups. Fifty-six individuals (28 young [18-35 years] and 28 old [65 years and over]) participated in this experiment. Subjective discomfort-glare rating scores on three different types of driver-side mirrors were assessed utilizing De Boer's rating scale in a controlled nighttime driving environment (laboratory ambient illuminant level-l lux with headlig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…The Maltese cross (near target) was presented in two different light intensities (figure 2b). In order to trigger accommodation at different light intensities, the Maltese cross was displayed by a laptop with two light intensity levels: 100 cd/m 2 and 20 cd/m 2 (Lockhart et al, 2006). …”
Section: Methodsmentioning
confidence: 99%
“…The Maltese cross (near target) was presented in two different light intensities (figure 2b). In order to trigger accommodation at different light intensities, the Maltese cross was displayed by a laptop with two light intensity levels: 100 cd/m 2 and 20 cd/m 2 (Lockhart et al, 2006). …”
Section: Methodsmentioning
confidence: 99%
“…A nine-point response range is often used to quantify the magnitude of discomfort due to glare, and for evaluations associated with outdoor lighting this is often known as the de Boer scale. De Boer scales have been used in studies associated with glare from outdoor lighting (Bullough et al 2008;Tashiro et al 2014;Villa et al 2017), vehicle headlamps (Christiansen et al 2009;Lockhart et al 2006;McLaughlin et al 2004;Reagan et al, 2016;Schmidt-Clausen and Bindels 1974;Sivak et al 1989;Theeuwes et al 2002), and interior lighting (Bangali 2015(Bangali , 2015Lin et al 2014). Figure 4 shows one example of the de Boer scale in which the descriptors of glare magnitude range from just noticeable to unbearable.…”
Section: Response Scalesmentioning
confidence: 99%
“…These too could influence driver behaviour. It is noteworthy that these effects of age were not in the anticipated direction: previous research has found that older drivers experience more glare, discomfort and other negative symptoms than younger drivers, 3,28,29 but age only correlated with headache and hours of driving. It is possible that the older drivers had modified their behaviour, due to glare, to reduce the amount of driving at night that they do.…”
Section: Discussionmentioning
confidence: 75%